INTER-RELIGIOUS EDUCATION IN THE QUR'AN: THE VALUES ANALYSIS OF INTER-RELIGIOUS EDUCATION IN THE QUR'AN - Imronudin; Riza Muhammad (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2023)
According to the Qur'an, this study concludes that inter-religious education is education with an anthropocentric orientation based on equality, togetherness, and justice in a democratic world with a pluralistic society. Humans are expected to carry out their functions with the values of tolerance, dialogue, cooperation, and brotherhood. This is in line with what is commanded by God in the Qur'an. Research and data analysis in this study uses qualitative-exploratory methods. In contrast, the approach used is philosophical-normative, meaning that it tries to dive to obtain actual activities that are rarely known and discussed. As a result, the Qur'an contains the values of inter-religious education, namely